A DNAzyme cascade for amplified detection of intracellular miRNA. Issue 70 (3rd August 2020) - Wu, Yanan; Li, Jing; Quan, Ke; Meng, Xiangxian; Yang, Xiaohai; Huang, Jin; Wang, Kemin
Abstract : Inspired by the natural enzyme cascade reaction, an artificial DNAzyme cascade system is developed for the amplified detection of intracellular miR-141. Abstract : Inspired by the natural enzyme cascade reaction, an artificial DNAzyme cascade system is developed for the amplified detection of intracellular miR-141. The results showed that the method enormously enhanced the readout of the fluorescence signal and achieved a femtomolar detection limit.